A new species of Glyptothorax (Teleostei: Sisoridae) from the Brahmaputra River basin, Arunachal Pradesh, India - Kosygin, Laishram; Singh, Pratima; Rath, Shibananda (Zootaxa, 2021)
Glyptothorax rupiri, a new sisorid catfish, is described from the Brahmaputra River basin in Arunachal Pradesh, northeast India. It differs from its congeners in the Indian subcontinent by the following combination of characters: the presence of plicae on the ventral surface of the pectoral spine and first pelvic-fin ray; a posteriorly serrated dorsal-fin spine, its length 11.3–12.2% SL; body depth at anus 11.2–13.4% SL; a thoracic adhesive apparatus longer than broad, with a V-shaped median depression which opens posteriorly; an arrow-shaped anterior nuchal plate element; adipose-fin base length 10.9–12.6% SL; nasal barbel not reaching anterior orbital margin; 14–18 serrae on posterior margin of the pectoral-fin spine; body with two longitudinal pale-cream stripes; densely tuberculated skin; and the presence of numerous tubercles on the dorsal surface of pectoral and pelvic-fin rays.